Idiopathic pure red cell aplasia: first report on CD8 positive lymphocytosis in bone marrow biopsy sections. Issue 10 (27th September 2005) - Ramadan, K M A; Anderson, J A M; McMullin, M F; Markey, G M
Abstract : There is no information in the literature regarding the lymphocyte content or type in bone marrow biopsies from patients with "idiopathic" pure red cell aplasia (PRCA). This report describes the bone marrow biopsy sections of a patient with PRCA. A diffuse CD3 positive (CD8 positive, granzyme B negative) lymphocytosis of approximately 1500/mm 3 was revealed by immunohistochemical staining. The extent of the T cell increase was not evident from morphological examination of the bone marrow aspirate or biopsy, from flow cytometric analysis of the aspirate, or from the peripheral blood lymphocyte count. Therefore, immunohistochemical analysis should be performed routinely in this rare disease and the data acquired may help to inform the choice of treatment.